Heavy metal accumulation in rosemary leaves and stems exposed to traffic-related pollution near Adana-İskenderun Highway (Hatay, Turkey) - Sert, Elif Bozdoğan; Türkmen, Musa; Çetin, Mehmet (Springer Science and Business Media LLC, 2019)
Pollution has become a problem on a global scale and poses a significant risk in terms of human health and natural ecosystems. Generally, the biggest sources of pollution are municipal and industrial facilities. However, traffic-related air pollution cannot be overlooked as a dangerous source either. There have been various methods of interventions to measure and reduce the risk and effects of traffic-related pollution. In the case of measuring, the use of certain plant species that can accumulate pollutants in their tissues is considered a practical solution. In this study, the aim is to find out the metals that are accumulated in rosemary leaves and stems and the rosemary leaves. In other words, the leaves and the stems are to be used as a biomonitors to reveal the rate of metal pollution along the highway. We try to identify the accumulation ability of traffic-related heavy metals (Al, Cd, Cr, Cu, Fe, Mn, Ni, Pb, and Zn) of the Rosmarinus officinalis L. (rosemary) which is used in the refuge and slopes along the highway connecting Adana with İskenderun (Hatay). Our findings concluded that the rosemary could have a decent capacity to accumulate Al, Cd, Cr, Cu, Fe, Mn, Pb, and Zn in both leaves and stem. We therefore believe that R. officinalis is a great tool in determining the amount of traffic-related pollution in urban areas.
Keywords: Chromium; Traffic-Related Pollution; Turkey; STEM (science, technology, engineering and mathematics); Cytotoxicity; Antimicrobial activity; Heavy metal accumulation; Procedures; Plants (botany); Turkey (republic); Nickel; Turkey (bird); Soil Pollutants; Risk assessment; Public health; Plant Stems; Soil pollutant; Plant leaf; Environmental monitoring; Bioaccumulation; Pollution; Health risks; Zinc; Biological monitoring; Chemistry; Rosmarinus officinalis L; Heavy metal; Heavy metals; Industrial facilities; Rosmarinus officinalis; Cadmium; Plant stem; Human; Environmental Monitoring; Iron; Stem; Adana [Turkey]; Accumulation; Antioxidant activity; Traffic-related air pollution; Metals, Heavy; Highway; Hatay; Humans; Cities; Ecosystem; Manganese; Atmospheric pollution; City; Urban area; Environmental exposure; Nonhuman; Perennial plant; Rosmarinus; Plant Leaves; Leaf; Lead; Heavy metal | Heavy metals | Tree bark; Air quality; Traffic emission; Rosemary; Geographic distribution; Copper; Aluminum; 11. Sustainability; 6. Clean water; 3. Good health; 15. Life on land; 13. Climate action